Odpowiedź :
Zadanie 6.
[tex]2^4*2^6=2^{10}\\4^2*2^4=(2^2)^2*2^4=2^4*2^4=2^8\\2^7:2^3=2^4\\(2^3*2^4):2^0=2^7:2^0=2^7\\2^{-3}*2^5=2^2\\2*2^4*2^5=2^5*2^5=2^{10}\\2^{-4}:2^{-6}=2^2\\(2^2)^3*2=2^6*2=2^7\\2*2^{15}:2^3=2^{16}:2^3=2^{13}\\2^{-6}:(2^6:2^{-4})=2^{-6}:2^{10}=2^{-16}[/tex]
Zadanie 7.
[tex]2^4*4^3*2^{-1}=2^4*(2^2)^3*2^{-1}=2^4*2^6*2^{-1}=2^{10}*2^{-1}=2^9\\4^3*2^4:8^{-4}=(2^2)^3*2^4:(2^3)^{-4}=2^6*2^4:2^{-12}=2^{10}:2^{-12}=2^{22}\\(16^{-2}:2^{-3})*4=((2^4)^{-2}:2^{-3})*2^2=(2^{-8}:2^{-3})*2^2=2^{-5}*2^2=2^{-3}\\(4^3)^{-2}:64^{-3}=4^{-6}:(2^6)^{-3}=(2^2)^{-6}:2^{-18}=2^{-12}:2^{-18}=2^6\\32^{-3}*(2^{-3})^{-5}=(2^5)^{-3}*2^{15}=2^{-15}*2^{15}=2^0\\(8^{-6}:4^{-6})^{-1}=(2^{-6})^{-1}=2^6[/tex]
Zadanie 8.
[tex]3^4*(81*9^{-6})^{-1}=3^4*(3^4*(3^2)^{-6})^{-1}=3^4*(3^4*3^{-12})^{-1}=3^4*(3^{-8})^{-1}=\\=3^4*3^8=3^{12}\\\\125^3*0,2^{-7}=5^3*(\frac{1}{5})^{-7}=5^3*5^7=5^{10}\\\\0,01*16*5^4=\frac{1}{100}*2^4*5^4=10^{-2}*2^4*5^4=10^{-2}*10^4=10^2\\\\2^4*9^2*36^{-5}=2^4*(3^2)^2*(6^2)^{-5}=2^4*3^4*6^{-10}=6^4*6^{-10}=6^{-6}\\\\32^{-2}:\left(64^3*(\frac{1}{2})^{-3}\right)=(2^5)^{-2}:((2^6)^3*2^3)=2^{-10}:(2^{18}*2^3)=\\=2^{-10}:2^{21}=2^{-31}\\[/tex]
[tex](\frac{2}{3})^{-3}*(\frac{27}{8})^{-3}*1,5=(\frac{2}{3}*\frac{27}{8})^{-3}*\frac{3}{2}=(\frac{9}{4})^{-3}*\frac{3}{2}=((\frac{3}{2})^2)^{-3}*\frac{3}{2}=(\frac{3}{2})^{-6}*\frac{3}{2}=(\frac{3}{2})^{-5}[/tex]